Electronic participation : 8th IFIP 8.5 International Conference, ePart 2016, Guimarães, Portugal, September 5-8, 2016, Proceedings /: 8th IFIP 8.5 International Conference, ePart 2016, Guimarães, Portugal, September 5-8, 2016, Proceedings. (2016) - Unknown
No abstract available